2014
DOI: 10.4141/cjps2013-228
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of mixing timothy with alfalfa for forage yield, nutritive value, and weed suppression in northern environments

Abstract: Bélanger, G., Castonguay, Y. and Lajeunesse, J. 2014. Benefits of mixing timothy with alfalfa for forage yield, nutritive value, and weed suppression in northern environments. Can. J. Plant Sci. 94: 51–60. Alfalfa can be grown alone or with a grass, but little information exists on the benefits of mixing alfalfa (Medicago sativa L.) with a grass in northern environments. Our objectives were (1) to determine the benefits in terms of forage yield, nutritive value, and weed suppression of mixing timothy (Phleum p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 29 publications
5
48
0
Order By: Relevance
“…Legume-grass mixtures generally provide more consistent forage yield across a wide range of environments than grass or legume monocultures (Sleugh et al 2000;Bélanger et al 2014). Legume-grass mixtures have also been shown to reduce weed invasion compared with monocultures (Tracy and Sanderson 2004;Picasso et al 2008;Frankow-Lindberg et al 2009;Sanderson et al 2012;Finn et al 2013;Bélanger et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Legume-grass mixtures generally provide more consistent forage yield across a wide range of environments than grass or legume monocultures (Sleugh et al 2000;Bélanger et al 2014). Legume-grass mixtures have also been shown to reduce weed invasion compared with monocultures (Tracy and Sanderson 2004;Picasso et al 2008;Frankow-Lindberg et al 2009;Sanderson et al 2012;Finn et al 2013;Bélanger et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Legume-grass mixtures have also been shown to reduce weed invasion compared with monocultures (Tracy and Sanderson 2004;Picasso et al 2008;Frankow-Lindberg et al 2009;Sanderson et al 2012;Finn et al 2013;Bélanger et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…From all management methods, only lucernegrass mixture significantly increased forage yield in accordance with the positive effect of mixture to dry matter yield (Bélanger et al 2014). Grass legume mixtures also resist weed invasion better than monocultures (Sanderson et al 2012), however some changes in forage nutritive value could be also observed (Bélanger et al 2014). In the Czech Republic, this technology is more applied in more humid regions (CR 5: 7.5°C, 600 mm; CR 7: 6.5°C, 700 mm) which are more favourable for grass components.…”
Section: Resultsmentioning
confidence: 69%
“…These farms also harvested lucerne at the bud stage which is in line with the best forage quality declared (Hakl et al 2010, Testa et al 2011. From all management methods, only lucernegrass mixture significantly increased forage yield in accordance with the positive effect of mixture to dry matter yield (Bélanger et al 2014). Grass legume mixtures also resist weed invasion better than monocultures (Sanderson et al 2012), however some changes in forage nutritive value could be also observed (Bélanger et al 2014).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation